POLA PENERAPAN MERDEKA BELAJAR PADA PEMBELAJARAN AL-ISLAM DAN KEMUHAMMADIYAHAN DALAM MENINGKATKAN DAYA KREATIFITAS PESERTA DIDIK DI SD MUHAMMADIYAH I KEBOMAS GRESIK: Pola Penerapan Merdeka Belajar Pada Pembelajaran Al-Islam dan Kemuhammadiyahan dalam Meningkatkan Daya Kreatifitas Peserta Didik Di SD Muhammadiyah I Kebomas Gresik - Muhammad Hambal Shafwan; Riza Agustina Wahyu Setiawati (Jurnal Staika: Jurnal Penelitian dan Pendidikan, 2023)
The focus of this research problem is: 1. What is the pattern of implementing Freedom of Learning in Al-Islam and Muhamdiyahan learning in increasing the creativity of students at SD Muhammadiyah I Kebomas Gresik? Students at SD Muhammadiyah I Kebomas Gresik?, and 3. How is the evaluation of the pattern of implementing Freedom of Learning in Al-Islam and Kemuhamdiyahan learning in increasing the creativity of students at SD Muhammadiyah I Kebomas Gresik? This research is field research with descriptive qualitative research methods. The subjects of this research were the Principal teachers, Deputy Head of Curriculum, Deputy Head of Al-Islam and Muhammadiyah and Al-Islam teachers using data collection methods through interviews, observation and documentation. Data analysis is carried out by collecting data, reducing data, presenting data, and drawing conclusions. The results of this research, the pattern of implementing freedom of learning in Al-Islam and Muhamdiyahan learning in increasing the creativity of students at SD Muhammadiyah I Kebomas Gresik. Researchers can see the results that learning is in favor of students and teachers as among, teachers as guides. The learning system among is that the teacher can give examples, provide habituation, teaching, behavior and inner and outer experiences. The results of the implementation of the Independent Learning Pattern in Al-Islam and Muhamdiyahan learning in increasing the creativity of students at SD Muhammadiyah I Kebomas Gresik. For students, teachers can always create a pleasant learning environment, and the learning objectives are clear and focused. Evaluation Results of Independent Curriculum Implementation Patterns Students are able to think critically, Students have emotional sensitivity, Students can develop their talents, Students have high imagination and creativity.